2011
DOI: 10.1177/03946320110240s313
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Allergic Reactions in Anesthetized Patients

Abstract: Hypersensitivity reactions during perioperative period are increasing and may be potentially life-threatening. Therefore, major emphasis is given to prevention. We perform a review to examine which measures should be taken to prevent reactions to products used in elective and emergency surgery. Any patient with a history of previous anaphylaxis or severe reaction during anaesthesia should be referred to allergist for detection of the offending compound. However, the identification of the triggering agent is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…Hypersensitivity or allergic reactions during the perioperative period are increasing and can be potentially life threatening. 5 It has been reported that these reactions are more common in atopic patients. 6 This is in keeping with our patient’s history of atopic disease, including asthma, allergic rhinitis, eosinophilia, and food allergy that may have increased his risk of having an allergic drug reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity or allergic reactions during the perioperative period are increasing and can be potentially life threatening. 5 It has been reported that these reactions are more common in atopic patients. 6 This is in keeping with our patient’s history of atopic disease, including asthma, allergic rhinitis, eosinophilia, and food allergy that may have increased his risk of having an allergic drug reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Caffarelli et al advised against relying on premedication because of the lack of documented evidence on its effectiveness in preventing allergic reactions to natural latex rubber [16]. The cost of extensive pre-surgery screening is also not justified for every patient [17].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prevention of anaphylaxis, some studies recommended the prophylactic use of these drugs [ 21 , 22 ]. Nevertheless, the results have been controversial or the benefits were limited to the allergic reaction caused by anesthetic agents [ 23 ]. In previous studies, by quantifying the amount of histamine released from mast cells, inhibitory effects of drugs or substances on the activity of mast cells were indirectly determined [ 24 , 25 ].…”
Section: To the Editormentioning
confidence: 99%